Church History Association of India: CHAI (Church History Association of India (CHAI), 2002)
"The Church History Association of India (CHAI) is an ecumenical body of those interested in the history of Christianity in India. Founded by Protestant Church historians in 1935, the CHAI had a flickering existence until late 1960’s, with its base at Serampore College, Kolkata. The entry of Catholic Church historians into CHAI was facilitated in the post-Vatican II period, which saw the beginning of a new ecumenical movement. Eventually CHAI became truly an ecumenical body of Church Historians representing many linguistic, regional and denominational groups"